The identification and control of an upper extremity exoskeleton for motor recovery - Zahari, Taha; Anwar, P. P. Abdul Majeed; M. A., Abdullah; I.M., Khairuddin; M.A., Zakaria; M. H. A., Hassan (Centre for Advanced Research on Energy (CARe), 2017)
This paper presents the model identification and control of an upper-limb exoskeleton system. The exoskeleton is intended for the rehabilitation of the elbow joint. The input-output measurement i.e. current and angular displacement of the actuator is used to identify the model via MATLAB System ldentification Toolbox. The identification plant is then used to pcrfom the Hardware in the Loop (HIL) simulation to identity apptopriate Proportional Derivative(PD) control gains prior to its employment of the actual exoskeleton system. It was established that the exoskeleton is able to track the joint trajectory prescribed with an acceptable error bounded between+/- 2.